A A Lexical-Pragmatic Analysis of COVID-19 Neologism in English and Kurdish - Kavi Shakir Mohammed (Zanco Journal of Humanity Sciences)
In the last two years, a worrying health phenomenon faced the whole world. This was due to the wide and quick spread of Coronavirus, COVID-19. It had its own effect on people’s life including language, linguistic changes and more specifically neologism and the interpretation of certain word meanings. This paper is an attempt to study the lexical pragmatic processes of narrowing and broadening including neologism of English and Kurdish-related words to COVID-19 from a relevance-theoretic perspective. Furthermore, it tries to know whether the processes of Lexical Pragmatics are the same in both languages with reference to the English selected words and their Kurdish counterpart. These aims are achieved by answering the following questions: first, how lexical-pragmatic processes are used within COVID-19-related lexicon? Second, to what extent the processes of lexical pragmatic processes of the selected items are equivalently the same in both languages? Accordingly, the paper is an analytic-qualitative one and the researcher selected and analyzed words from English and their counterpart in Kurdish, as well, to inspire neologism from a pragmatic point of view. The data is taken from 12 WHO’s Director-General statements and updates on the COVID-19 pandemic meanwhile the Kurdish counterparts were taken from 22 official declarations and statements, related to COVID-19, issued by both Ministry of Health and Ministry of Interior of Kurdistan Regional Government. The analysis shows that lexical pragmatics is an applicable approach in studying and analyzing the encoded meaning of the words and expressions used by the speaker through which the importance of relevance theory is highlighted in realizing the embedded meaning without relying on other Grice’s maxims. Furthermore, it is concluded that the contextual knowledge shared by the speaker and hearer is a good resource for generating ad hoc concepts. Moreover, both processes of lexical narrowing and broadening- neologism are studied in which the narrowed lexical items are more frequently detected than broadening in both languages.